Long-term survival in patients with coronary artery disease undergoing percutaneous coronary intervention with or without intracoronary pressure wire guidance: a report from SCAAR. (25th November 2020) - Volz, S; Redfors, B; Dworeck, C; Petursson, P; Gotberg, M; Jernberg, T; Linder, R; Ramunddal, T; Frobert, O; Witt, N; James, S; Erlinge, D; et al.
Abstract: Background: Intracoronary pressure wire measurements of fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) provide decision-making guidance during percutaneous coronary intervention (PCI). However, limited data exist on the impact of FFR/iFR on long-term clinical outcomes in patients with stable angina, unstable angina (UA)/non-ST-segment elevation myocardial infarction (NSTEMI), or STEMI. Methods: We used data from the Swedish Coronary Angiography and Angioplasty Registry (SCAAR) on all patients in Sweden undergoing PCI (with or without FFR/iFR guidance) for stable angina, UA/NSTEMI, or STEMI between January 2005 and March 2018. The primary endpoint was all-cause mortality and the secondary endpoints were stent thrombosis or restenosis and periprocedural complications. The primary model was multilevel Cox proportional-hazards regression using an instrumental variable (IV) to adjust for known and unknown confounders with treating hospital as a treatment-preference instrument. The following variables were entered into Cox proportional-hazards regression in addition to the IV: age, sex, diabetes, indication for PCI, severity of coronary disease, smoking status, hypertension, hyperlipidemia, previous myocardial infarction, previous PCI, previous coronary artery bypass graft, type of stent. Results: In total, 151, 001 patients underwent PCI: 31, 514 (20.9%) for stable angina, 74, 982 (49.6%) for UA/NSTEMI, and 44, 505 (29.5%) for STEMI. Of these, FFR/iFR guidance was used in 11, 433 patients (7.6%): 5029 (44.0%) with stable angina, 5989 (52.4%) with UA/NSTEMI, and 415 (3.6%) with STEMI; iFR was used in 1156 (10.1%) of these patients. After a median follow-up of 1784 (range 1–4824) days, the FFR/iFR group had lower adjusted risk estimates for all-cause mortality [hazard ratio (HR) 0.79; 95% confidence interval (CI) 0.69–0.91; P=0.001] and stent thrombosis and restenosis (HR 0.13; 95% CI 0.09–0.19; P<0.001). The number of periprocedural complications did not differ significantly between the groups (odds ratio 0.69; 95% CI 0.30–1.55; P=0.368). There was no interaction between FFR/iFR and indication for PCI. We found no difference between FFR and iFR (HR 1.12; 95% CI 0.90–1.59; P=0.216). Conclusions: In this observational study, the use of FFR/IFR was associated with a lower risk of long-term mortality in patients undergoing PCI for stable angina, UA/NSTEMI, or STEMI. Our study supports the current European and American guidelines for the use of FFR/iFR during PCI and shows that intracoronary pressure wire guidance has prognostic benefit in patients with stable angina as well as in patients with the acute coronary syndrome. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Heart and Lung Foundation, ALF Västra Götaland, Swedish Scientific Council